Dançando com gatos e passáros: O movimento ecossistêmico da ludopoiese na educação infantil - Pinheiro, Evanir de Oliveira (2011)
This study shows the movement of educators ludopoiese ecosystem of the Center for Early Childhood Education Marise Paiva-CEIMAP. We used the metaphorof dance as an opportunity to stimulate scientific creativity. Ecosystem Thought, complex thinking, the theory of autopoiesis and Flow Theory, constituted the main theoretical steps to understand the phenomenon of ludopoiese, from the look of your totalidadem with the following objectives: 1 - Identify and interpret the process of self ludopoiética CEIMAP of Early Childhood Educators in the actions of the play, care for and educate in school life; 2 - Analyze Ecosystem Thought from ludopoiéticos how these processes affect and / or possible changes and transformations in practice humanescenteseducational CEIMAP. The theoretical metodógicos steps to address the proposed objectives are grounded in existential action research part of the appreciation of the complexity of the real, considering the human being a whole dynamic. In this sense the game of sand, recreational experiences, the systematic studies and video training were explored with a view to the transdisciplinary relevance of everyday phenomena. New knowledge acquired in accordance with the directions given indicating the movement of the ecosystem studied ludopoiese educators, involved in four main streams: love, play, care for and raise it from love streamline interdependently. The ludopoiese eachteacher would then be fed by this web generated by love that permeates all other educational activities, nurturing and maintaining a constant creative self-organization of knowledge and know-how to be teachers. Thus, every network that generates andstream lines the system emerges ludopoiético biology of love, the open dialogue and playing in the wishing well to the student, the aesthetic beauty of caring and educating, as a human conditionand relevant as possible to live / live not only in teaching children, but in other educational contexts of teaching and teacher education